Investors Satisfaction Towards Stock Market In Thoothukudi City - et. al., Dr. G. Paulraj, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The globalization of economic markets has been raise the size of the society of retail investors’ in excess of the past two decades by providing a wide range of market and investment options. Therefore, it makes their investment decisions development more multifaceted. The factors influence investor’s awareness are return on investment, market trend or risk, short term profitability, price of the share, dividend policy, past financial presentation, company character, standing of the board, current earnings of the company and specialist judgment. This study focuses investor satisfaction towards stock market in Thoothukudi city